Paleomagnetic evidence for late Cenozoic glaciations in the Mackenzie Mountains of the Northwest Territories, Canada (Dataset) ... - R. W. Barendregt; R. J. Enkin; J. Baker; A. Duk-Rodkin (Magnetics Information Consortium (MagIC), 2010)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic evidence for late Cenozoic glaciations in the Mackenzie Mountains of the Northwest Territories, Canada ...